Ritualizing Tolerance: How Shared Imtaq Practices Govern Religious Coexistence in a Plural Secondary School - Nuraeni; Mustain; Deddy Ramdhani (Journal of Religious Studies, 2025)
This study explores how shared IMTAQ practices operate as an institutional mechanism for governing religious coexistence within a plural secondary school setting. Departing from dominant approaches that frame religious tolerance as a curricular objective or moral instruction, this research reconceptualizes tolerance as a ritualized social process embedded in everyday institutional routines. Using a qualitative case study design, the study was conducted in a multi-religious public secondary school where students from different faith traditions participate in IMTAQ activities simultaneously. Data were generated through in-depth interviews with school leaders, teachers representing different religious backgrounds, and students, supported by sustained participant observation and analysis of institutional documents. The findings demonstrate that IMTAQ functions as a form of soft governance through ritual synchronization, spatial openness, and normative regulation, allowing religious diversity to be managed through shared practices rather than formal theological dialogue. These ritual arrangements normalize interreligious presence, reduce symbolic boundaries, and cultivate a stable pattern of religious coexistence without requiring doctrinal alignment or explicit tolerance discourse. Tolerance, in this context, emerges as a lived disposition shaped through repeated participation in institutionally structured rituals rather than as an abstract value transmitted through instruction. The significance of this study lies in its contribution to the sociology of religion and religious governance by highlighting how everyday ritual practices within educational institutions can regulate pluralism and sustain social cohesion. By shifting analytical attention from religious teaching to ritual governance, this study offers a novel perspective on how tolerance is produced, embodied, and maintained in plural societies, extending current debates on lived religion and institutional responses to religious diversity.